50.4: Relation between Short‐term and Long‐term Assessment of Glare. Issue 1 (June 2015) - Chen, Yanda; Tu, Yan; Zhang, Jihuang; Lu, Fan; Liu, Lu; Wang, Lili; Peng, Sheng; Heynderickx, Ingrid
Abstract : By combining two experiments, we evaluated to what extent short‐term evaluation of discomfort glare is a good prediction for long‐term exposure to the same lighting condition. The results indicated that glare reported after long time exposure was equal or slightly lower than what was assessed after short‐term exposure, reducing the need for longer‐term experiments.